A design of experiments approach to the sensitivity analysis of the life cycle cost of biodiesel - Khang, Dinh S. (Animo Repository, 2018)
Economic feasibility is one of the major factors that has to be considered in the decision to continue with alternative fuel development. Economic feasibility of these alternatives can be assessed through life cycle costing, which is dependent on volatile parameters such as feedstock price, operating rate, capacity, interest rate and conversion efficiency. Uncertainty analysis is necessary to determine the robustness of the life cycle cost estimates. In this study, design of experiments was demonstrated to be an effective approach to analyze the sensitivity of life cycle cost to these parameters. Furthermore, the sensitivity analysis can be done based not only on the individual effects, but also on the interactions of parameters. Data from the biodiesel program of Vietnam were used as a case study. The results show that operating cost and feedstock price have the most significant effects on biodiesel cost followed by capacity, interest rate and conversion efficiency. Interactions were observed between conversion efficiency and feedstock price; interest rate and operating rate; and feedstock price and interest rate. The regression equation obtained from sensitivity analysis shows that the cost of jatropha biodiesel is 0.72–1.02 US$/L, the cost of fish oil biodiesel is 0.45–0.87 US$/L, and the cost of waste cooking oil biodiesel is 0.42–0.61 US$/L. Although the framework developed in this study was used specifically in the life cycle costing of biodiesel, it can be readily applied to other low-carbon energy systems in the future. © 2017, Springer-Verlag GmbH Germany.